Tax Evasion as a Crime: A Survey of Perception in Yemen - Aljaaidi, Khaled Slamen Yaslam; Abdul Manaf, Nor Aziah; Karlinsky, Stewart S. (Canadian Center of Science and Education, 2011)
This paper explores the perception of Yemeni citizens of the severity of tax evasion relative to other crimes and violations. Perception of tax evasion may somewhat explain the degree of non-compliance with the tax laws. Using data from a self- administered survey and a personnel structured interview, the results of mean and comparative analysis show that tax evasion items were ranked as the three least crimes of 30 listed crimes. Further, Tax evasion is categorized the least serious category out of six categories. The results of this study should be useful to policy makers in Yemen and elsewhere, as it was found that there is an alarming signal that tax evasion is relatively ranked as the least serious offence, which could lead to an environment where taxpayers may not be afraid of cheating on their tax returns.